Microwave non-destructive testing for processed and unprocessed palm oil using free space microwave measurement system in 18 - 26 GHz frequency range / Nur Raihana Abd Wahab - Abd Wahab, Nur Raihana (2009)
This thesis presents the measurement and analysis at 18-2 6 GHz frequencies range for two difference sample oils, processed and unprocessed palm oil using free space microwave measurement (FSMM) system. The measurement system consist a pair of spot focusing horn lens antenna, mode transitions, coaxial cables, vector network analyzer (VNA) and computer. S-parameter measurements in free space were measured by VNA system. Complex permittivity and loss factor of samples are calculated by Fortran PowerStation 4.0 software.